Early Treatment-Resistance in First Episode Psychosis - Fernando, Piyumi; Strauss, Johanna; Wagner, Elias; Löhrs, Lisa; Campana, Mattia; Falkai, Peter; Hasan, Alkomiet; Papazova, Irina (Pharmacopsychiatry, 2024)
Introduction Approximately 30% of individuals with schizophrenia experience treatment resistance (TR), with 70% exhibiting it from the onset. Most research fails to distinguish between acquired and innate resistance, with limited data on TR in first episode psychosis (FEP). However, FEP patients with TR experience progressively worse outcomes compared to those with initial response. To further understand these findings, clinical and demographic data of FEP patients with and without TR were compared in this naturalistic study.Methods Information was extracted on FEP patients who were antipsychotic-naive at the time of admission from a retrospective database on F2x diagnosed patients admitted to the LMU psychiatric clinic between 2008 and 2018. Clozapine was used at discharge as a marker of TR in the FEP cohort. A similarly antipsychotic-naïve FEP control group without clozapine at discharge, was generated by matching for gender and age. Thirty clinical and demographic variables were analyzed to identify differences.Results Two-hundred forty antipsychotic-naive FEPs were included: 33 with clozapine at discharge (TRC group), and 207 in the control group (non-TRC). Significant differences were observed in inpatient stay duration, chlorpromazine-equivalent dosage, number of antipsychotics, and anticholinergic medication at discharge.Discussion The findings indicate that longer inpatient stay, an increased number of antipsychotics, and possibly a more extended prodrome may serve as markers for non-clozapine TR in FEP. Further research is necessary to establish the robustness of these variables as early-stage TR markers.
Keywords: treatment-resistance; psychosis; clozapine; schizophrenia; treatment-response